PENCEGAHAN BULLYING ANAK USIA SEKOLAH DASAR MELALUI KEGIATAN SOSIALISASI - Asrorurrosyidin, Muhammad; Alya, Nadifa; Dwitasari, Rahma Ayu; Ayurveda, Azzahra Aisyah (UNIVERSITAS SERAMBI MEKKAH, 2024)
The benefits of holding this activity are as an effort to increase the knowledge and understanding of elementary school-age children related to bullying in children at SDN Plosogeneng 1. The existence of this “Anti-Bullying” Socialization is an alternative that is carried out as an effort to prevent and reduce bullying behavior in school-age children with their peers. Community service activities have involved educational institutions, namely Plosogeneng 1 State Elementary School as partners, namely 12 teachers and 40 students as a whole, as well as a team of MBKM Internship Students from the Faculty of Law, UPN “Veteran” East Java. The results of community service activities in this elementary school stated that the increase in children's knowledge and understanding of bullying actions, namely 30 children out of a total of 40 children were in the very knowledge category. The knowledge gained is in the form of understanding bullying, types of bullying, the impact of bullying on victims, prevention of bullying by students, prevention of bullying by the community, and prevention of bullying by schools.